Building infrastructure and operating-technological options in post-COVID-19 oral health care (Research, Society and Development, 2020)
During the COVID-19 pandemic, concerns about the impact of the aerosol generated in dental procedures on the spread of disease led to additional infection control measures that will remain as part of the biosafety routine after the end of the pandemic. This article addresses a little discussed topic that concerns the need to adapt the physical space and operational-technological choices for post-COVID dental care19. The current architecture of spaces for dental care in teaching and public health service units allows the care of several patients simultaneously. However, aerosols are produced routinely during dental procedures, with a real possibility of contamination between different patients. In this way, we present perspectives and suggestions for readjusting these spaces for teaching units and public health services in the short, medium and long term and also for using the resources of Information and Communication Technologies and minimally invasive dentistry.